Vitamina C em pimentas e pimentões (Capsicum spp): (Vᵃ comunicação sobre vitamina C) - Cambraia, José; W D Casali, Vicente; Brune, Walter; A A Couto, Flávio (Revista Ceres, 2025)
This paper deals with Vitamin C contents of some varieties of sweet and hot pepper of the species Capsicum annuum, C. sinense, C. pendulum, C. frutescens, C. microcarpum and C. praetermissum, all cultivated in Brazil.